Bayesian Network Modeling Applied to Feline Calicivirus Infection Among Cats in Switzerland - Kratzer, Gilles; Lewis, Fraser I.; Willi, Barbara; Meli, Marina L.; Boretti, Felicitas S.; Hofmann-Lehmann, Regina; Torgerson, Paul; Furrer, Reinhard; Hartnack, Sonja (Frontiers in Veterinary Science, 2020)
Bayesian network (BN) modeling is a rich and flexible analytical framework capable of elucidating complex veterinary epidemiological data. It is a graphical modeling technique that enables visual presentation of multi-dimensional results while retaining statistical rigor in population-level inference. Using previously published case study data about feline calicivirus (FCV) and other respiratory pathogens in cats in Switzerland, a full BN modeling analysis is presented. The analysis shows that reducing the group size and vaccinating animals are the two actionable factors directly associated with the FCV status and are primary targets to control for FCV infection. The presence of gingivostomatitis and Mycoplasma felis are also associated with FCV status, but signs of upper respiratory tract disease (URTD) are not. FCV data is particularly well-suited to a network modeling approach as both multiple pathogens and multiple clinical signs per pathogen are involved, along with multiple potentially interrelated risk factors. BN modeling is a holistic approach - all variables of interest may be mutually interdependent - which may help to address issues such as confounding and collinear factors, as well as disentangle directly versus indirectly related variables. We introduce the BN methodology, as an alternative to the classical uni- and multivariable regression approaches commonly used for risk factor analyses. We advice and guide researchers about how to use BNs as an exploratory data tool and demonstrate limitations and practical issues. We present a step-by-step case study using FCV data along with all code necessary to reproduce our analyses using the open source R environment. We compare and contrast the findings of the current case study using BN modeling with previous results which used classical regression techniques, and we highlight new potential insights. Finally, we discuss advanced methods such as Bayesian model averaging, a common way of accounting for model uncertainty in a Bayesian network context.